Integrating E-Collaboration and Equity Crowdfunding in Smart Village Governance for Sustainable Tourism Development - Andre Ariesmansyah; Ferdyansyah Wicaksono (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
This study examines the fragmentation of tourism village governance across three critical dimensions digital governance, collaborative governance, and financial accountability and proposes an integrated e-collaboration smart village model grounded in equity crowdfunding principles. Set in Gunung kuning Village, Majalengka Regency, West Java, Indonesia, the study employs an exploratory qualitative approach, combining semi-structured in-depth interviews with key governance informants, field observations, document review, and a Small Group Discussion. Thematic analysis was conducted using ATLAS.ti to ensure analytical rigor and transparency. The findings reveal that digital governance in the village remains confined to administrative and promotional functions, with no integrated digital coordination system among governance actors. Collaborative governance is largely informal, relying on interpersonal networks rather than institutionalized mechanisms, while financial governance lacks transparency instruments and innovative financing alternatives. Equity crowdfunding emerges as a theoretically promising but practically underutilized financing mechanism and is examined in this study as a prospective governance-financing pathway rather than an empirically implemented intervention. On this empirical basis, the study develops a four-layer hybrid governance model comprising Input, Governance Process, Readiness, and Output layers that integrates digital systems, structured multi-stakeholder collaboration, and accountable financial mechanisms. The proposed model is primarily conceptual in nature, as equity crowdfunding has not yet been implemented in the study site. It constitutes a theoretical contribution to public administration and rural governance scholarship by bridging the previously fragmented literatures on smart villages, e-collaboration, and participatory financing within a single analytical framework applicable to Indonesian tourism villages.